E-Business - Parag Kulkarni; Sunita Jahirabadkar; Pradip Chande (India Oxford University Press, 2019)
E-business is a comprehensive textbook designed to meet the needs of students of post graduate management programmes. It integrates e-commerce with strategic aspects of e-business and illustrates them through numerous examples, exhibits, figures, and case studies. The book covers different aspects of e-business including e-business strategies, various e-business models and life cycle, business intelligence and knowledge management in Indian and global context. It also covers setting up of e-business and its management and techno-managerial aspects of running e-business. The book is equipped with real life case studies of India-based e-business companies. Users would find this book useful for its coverage of the various aspects of e-business. It would also serve as a good reference book for marketing and IT professionals and e-business practitioners.
Keywords: Business; Textbooks; E-business; Global Digital Business (BIN2042-N)